NLRX1 Is a Multifaceted and Enigmatic Regulator of Immune System Function - Nagai-Singer, Margaret A.; Morrison, Holly A.; Allen, Irving C. (Frontiers in Immunology, 2019)
Over the last decade, significant progress has been achieved in defining mechanisms underlying NLR regulation of immune system function. However, several NLR family members continue to defy our best attempts at characterization and routinely exhibit confounding data. This is particularly true for NLR family members that regulate signaling associated with the activation of other pattern recognition receptors. NLRX1 is a member of this NLR sub-group and acts as an enigmatic regulator of immune system function. NLRX1 has been shown to negatively regulate type-I interferon, attenuate pro-inflammatory NF-κB signaling, promote reactive oxygen species production, and modulate autophagy, cell death, and proliferation. However, the mechanism/s associated with NLRX1 modulation of these pathways is not fully understood and there are inconsistencies within the field. Likewise, it is highly likely that the full repertoire of biological functions impacted by NLRX1 are yet to be defined. Recent mouse studies have shown that NLRX1 significantly impacts a multitude of diseases, including cancer, virus infection, osteoarthritis, traumatic brain injury, and inflammatory bowel disease. Thus, it is essential that the underlying mechanism associated with NLRX1 function in each of these diseases be robustly defined. Here, we summarize the current progress in understanding mechanisms associated with NLRX1 function. We also offer insight into both unique and overlapping mechanisms regulated by NLRX1 that likely contribute to disease pathobiology. Ultimately, we believe that an improved understanding of NLRX1 will result in better defined mechanisms associated with immune system attenuation and the resolution of inflammation in a myriad of diseases.